Use of small specimen creep data in component life management: a review - Craddock Dyson, Charles; Sun, Wei; Hyde, Christopher J.; Brett, Steve J.; Hyde, Thomas H. (Taylor and Francis, 2016)
Small specimen creep testing techniques are novel mechanical test techniques that have been developed over the past 25 years. They mainly include the sub-size uniaxial test, the small punch creep test, the impression creep test, the small ring creep test and the two-bar creep test. This paper outlines the current methods in practice for data interpretation as well as the state-of-the-art procedures for conducting the tests. Case studies for the use of impression creep testing and material strength ranking of creep resistant steels are reviewed along with the requirement for the standardisation of the impression creep test method. A database of small specimen creep testing is required to prove the validity of the tests.